The State of Fundamental Rights during CORONA Pandemic - Gupta, Saurabh; Bhol, Seema Gupta (International Journal of Law, Human Rights and Constitutional Studies, 2022)
Global spread of corona virus touched India in January end of 2020. No tried and tested treatment of this new virus made Govt. of India announcing nationwide lockdown. Lockdown was looked upon as need of the hour. The side effects of lockdown were not less serious as the problem of corona disease itself. The economic condition of both people as well as Govt, exchequer starts worsening. Lockdown have an impact on Fundamental Rights of the people which are guaranteed by the Constitution of India. The Present paper tries to analyze the condition of fundamental rights of Indian citizens.